ВИКОРИСТАННЯ МАРКЕТИНГОВИХ ПІДХОДІВ У СФЕРІ РЕСТОРАННОГО БІЗНЕСУ УКРАЇНИ - Cherdantseva, Iryna; Klypach, Andriy (Збірник наукових праць Черкаського державного технологічного університету. Серія: Економічні науки, 2019)
The article deals with the general tendencies of development of the restaurant market of Ukraine. It is noted that the use of marketing approaches in the intensification of competition among the enterprises working in the sphere of restaurant business, it is necessary to exercise purposeful influence on the market in order to promote their establishments. Noted by the need to take into account the marketing component is a guarantee of how well the restaurant will function. The analysis shows that at present the number of restaurant establishments has exceeded the pre-crisis indicators, however, there is a decrease in the growth rate of the segment. The most attractive conditions for development are noted in the regions, with poor development of infrastructure, insufficient purchasing power and obstacles of local authorities. It has been established that the Ukrainian restaurant began reformatting, among the main reasons being the profitability of investing in the restaurant business, lower prices for the services of designing, design and technical equipment of the restaurant business, changing the purchasing behavior of the population towards eating outside the home.
THE USAGE OF MARKETING APPROACHES IN THE RESTAURANT BUSINESS OF UKRAINE
Keywords: ресторанний бізнес; маркетингові інструменти; структура ресторанного ринку; кейтеринг; евент-дигустації; дизайн ресторану; ІТ-інструменти; інтерактивні карти; перехресний маркетинг; restaurant business; marketing tools; structure of restaurant market; catering; event tastings; restaurant design; IT tools; interactive maps; cross marketing